FACTORS ASSOCIATED WITH DIARRHEA DISEASE IN CHILDREN 1-5 YEAR IN PUSKESMAS WORK AREA PAMATANG RAYA DISTRICT SIMALUNGUN 2020 - Sihombing, Eka; Marchese, Malvina; Samosir, Alexander; Aulia Nanda, Ficha; Sihombing, Chintani (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Diarrheal disease is a condition where the frequency of defecation is more than 4 (four) times in infants and more than 3 (three) times in children, the consistency in children is watery, can be green in color or can also be mixed with mucus and blood that occurs in children under five. occurs as a result of a person's lack of information or knowledge. This research was conducted in the Working Area of the Pamatang Raya Health Center, Simalungun Regency from August to September 2020, the sample size was 71 people using an analytical quantitative method through a cross-sectional approach. Data collection using secondary data was analyzed using the chi-squere bivariate test. The results showed that in the good knowledge category there were 15 people (21.1%), enough knowledge 26 people (36.6), less knowledge 30 people (42.3), negative attitudes were 47 people (66.2%), positive attitudes were 24 (33.4), good mother behavior were 26 people (36.6), poor behavior were 30 people (42.3%). The conclusion from the study is that there is a relationship between knowledge, attitudes, and behavior of mothers towards diarrheal disease in toddlers at the Pamatang Raya Health Center.